Alpha-2-adrenoceptor control of cortisol and ACTH in normal volunteers: preliminary open trial of the effects of acute and chronic idazoxan. - Glue, P; Wilson, S; Campling, G; Knightly, M; Franklin, M; Cowen, P; Nutt, D (1992)
To examine the role of alpha 2-adrenoceptors in the control of cortisol and ACTH, hormone responses to the selective alpha 2-antagonist idazoxan were studied in 12 normal volunteers. Plasma cortisol and ACTH were measured from 0930h-1230h on three occasions: before, on the 1st day, and on the 22nd day of an open treatment trial with idazoxan 40 mg administered three times per day. Compared with pretreatment cortisol levels, acute but not chronic idazoxan treatment attenuated the normal diurnal fall in plasma cortisol. Plasma ACTH concentrations were not altered by either dose of idazoxan. The attenuation of the diurnal fall in cortisol after acute idazoxan may be mediated through increased central availability of norepinephrine, and is similar to responses after high doses of the less selective alpha 2-antagonist yohimbine. Activity of central noradrenergic neurons appears to be reduced or normalized by chronic idazoxan, indicated by restoration of the normal diurnal fall in cortisol.